Transforming the Urban Space through Transit-Oriented Development : The 3V Approach - Salat, Serge; Ollivier, Gerald (World Bank, Washington, DC, 2017)
Imagine a city that is more competitive, with higher-quality neighborhoods, lower infrastructure costs, and lower C02 emissions per unit of activity. This city has lower combined transportation and housing costs for its residents than other cities at similar levels of economic activity. Its residents can access most jobs and services easily through a combination of low-cost public transport, walking and cycling. Its core economic and population centers are resilient to natural hazards. It is able to finance improvements to public space, connectivity, and social housing by capturing value created through integrated land use and transport planning. Such a vision has never been more relevant for rapidly growing cities than it is today. Transit-oriented development (TOD) can play a major role in achieving such a vision. Based on an observation of methodologies applied in different countries, the World Bank's Community of Practice on Transit Oriented Development has developed a methodology called the 3 Value (3V) Framework, which outlines a typology to facilitate TOD implementation at the metropolitan and urban scale in various contexts. The 3V Framework equips policy and decision makers with quantified indicators to better understand the interplay between the economic vision for the city, its land use and mass transit network, and urban qualities and market vibrancy around its mass transit stations. This book provides examples of approaches taken by cities like London and New York to align their economic, land use, and transport planning to generate jobs and high value. We hope this book will help readers develop a coherent vision, policies, and strategy to leverage the value created through enhanced connectivity and accessibility and make cities even more appealing places to live, work, play and do business.